Current and emerging approaches to cochlear immunosuppression with translation to human inner ear stem cell therapy: A systematic review. - Nathan J Creber; Jameel Muzaffar; Shravan Gowrishankar; Daniele Borsetto; Veronica Phillips; Matthew E Smith (PLoS ONE)
Hearing loss is a significant health burden across all stages of life. One in 5 people suffer hearing loss, with 5% of the world's population experiencing disabling hearing loss. A large proportion of this loss is the consequence of damage or loss of neurosensory structures, termed "sensorineural" hearing loss. A recent advance in the treatment of sensorineural hearing loss has occurred, with the advent of inner ear stem cell therapy. Focus has pivoted from augmenting existing neural structures to regenerating neural frameworks. To date, stem cell therapy is limited by the host immune system and rejection of donor cells. A better understanding of immunity in the inner is ear required to progress stem cell therapy for hearing loss. This review outlines a contemporary understanding of the inner ear immune system. We discuss concepts of immune dysregulation that may lead to common inner ear pathologies, and, in doing so, review the efficacy of current pharmacotherapies that mitigate end organ damage through a process of immunosuppression. Current literature is appraised through a systematic review exploring two areas of focus; immunosuppression therapies for the treatment of inner ear pathology associated immune dysregulation, and, subsequently, the efficacy of immunosuppressive agents in translational models of inner ear stem cell therapy. Through greater understanding of these concepts, and systematic appraisal of the literature, this review summarises the literature for contemporary immunosuppressive regimes that may facilitate stem cell accommodation in the cochlea and auditory nerve.